Microglia and Other Myeloid Cells in Central Nervous System Health and Disease - Gopinath, Adithya (J Pharmacol Exp Ther, 2020)
Mononuclear macrophages derived from the bone marrow (myeloid cells) are key cellular components of the innate immune system in different organs. In this minireview, we are focused on both brain and blood macrophages, known as microglia and monocytes, respectively. We provide a succinct summary of the cells’ functions under both normal and pathologic conditions, with particular reference to common neurodegenerative disorders, such as Alzheimer and Parkinson disease. SIGNIFICANCE STATEMENT: In this minireview, we aim to summarize available literature on microglial and myeloid involvement in CNS disease, directing the reader toward relevant and translatable interpretations of myeloid cell function in CNS health and neurodegeneration.